Monitoring of aviation personnel potential according to the competence approach - Koshekov, Kayrat; Kalekeyeva, Marina; Seidakhmetov, Beken; Kaliyeva, Gulzhan; Assilbekova, Indira; Gozhakhmetova, Madina (Eastern-European Journal of Enterprise Technologies, 2024)
The object of the study is the personnel potential of aviation. The paper considers the problem of the effectiveness of monitoring the quality of airline personnel. According to the results of the study, it was stated that the stable growth in the volume of international cargo and passenger air transportation requires full-fledged provision of aviation with highly qualified specialists, a shortage of which has been observed in airlines in most countries of the world for several years. It is emphasized that a shortage of highly qualified specialists can be avoided only with the introduction of monitoring of the qualitative composition of the aviation personnel potential according to the competence approach. An algorithm has been developed for monitoring the qualitative composition of human resources based on the audit of compliance of professional competencies of civil aviation personnel with international standards of ICAO (International Civil Aviation Organization), EASA (European Union Aviation Safety Agency), IATA (International Air Transport Association) using triangulation of mixed methods. The expediency of using the monitoring results as a fundamental basis for building a centralized information platform with open access to information resources on the qualitative composition of the personnel potential of airlines and the industry is justified. It is reasonable that the implementation in practice of the algorithm for monitoring human resources according to the competence approach will allow stakeholders to have a clear understanding of the level of professional competence of personnel and the need to improve it in the short term, which will accelerate the elimination of the existing shortage of highly qualified specialists by timely taking measures to amend state programs for training civil aviation specialists, improving their qualifications and certification. It is emphasized that the application of this algorithm is possible in the presence of a sectoral qualifications framework